THE IMPACT OF CREDIT GRANTING DECISIONS ON THE QUALITY OF ELECTRONIC ACCOUNTING DISCLOSURE - A. P. Dr. Khalid Sabah Ali; Researcher Ayman Abdel-Wadoud Hamed (Scholars Digest Publishing, 2023)
The research aims to strengthen the theoretical knowledge of electronic accounting disclosure and demonstrate its importance to Iraqi commercial banks, and the need to strengthen the capabilities of banks to carry out electronic disclosures to keep pace with international banks, which improves the quality of disclosure, as well as revealing the most prominent obstacles to the application of electronic disclosure in the Iraqi environment, with a statement of its impact on rationalizing decisions Granting credit and the questionnaire was used to test this relationship by using a set of appropriate statistical methods to analyze the research variables to indicate the impact and correlation, by using the statistical program (SPSS), and the questionnaire was distributed to a number of workers in private commercial banks, amounting to (203) workers. (190) questionnaires were answered, and (13) questionnaires were excluded. Through the results of these questionnaires, the researcher reached a set of conclusions, the most important of which is that electronic accounting disclosure contributes to improving the quality of disclosure tremendously in order to provide information to all parties, which makes it easier for them to conduct direct analyzes, comparison and take appropriate decisions. It became clear from the results of the statistical analysis that there is a statistically significant correlation between the research variables (the quality of the electronic accounting disclosure, and credit granting decisions), and the value of the correlation coefficient between them was positive value, which means that the relationship is direct between the search variables, and it became clear from the results of the statistical analysis that there is a statistically significant effect relationship between the search variables (and the quality of the electronic accounting disclosure, and credit-granting decisions), and the sign of the beta coefficient between them was positive, which means that the effect is positive (a direct relationship).And the most important thing recommended by the researcher is to increase the awareness of local banks by using advanced technologies represented, especially with regard to international communication networks and computers, to raise the quality of disclosure, because it represents the cornerstone of the electronic accounting disclosure process, and that Iraq must join the XBRL organization as an electronic language that was specially developed to support disclosure. Just like Kuwait, UAE, Jordan, and Saudi Arabia did and benefit from the XBRL organization.
Keywords: The decision to grant credit, the quality of the electronic accounting disclosure.